(untitled) (Al-Academy, 2026)
Good design refers to the ability of a building to meet specific needs and benefits. If the design fails to fulfill this role، the building can be diverted to other، more appropriate، utilitarian uses. Therefore، the work of interior functions should not be a product of the structure، nor should the structure duplicate the work. When combining form in two directions، the first is to ensure utilitarian function within a space or group of spaces—a utilitarian design principle—and the second is to use shapes in an aesthetically creative way within the space or spaces—a modern design principle. The use of irregular shapes poses a challenge for those interested in interior design. Design in general، and interior planning in particular، is still in dire need of the latest trends that interest experts in this field. This creative implementation has been accompanied by tremendous development and an expansion in the scope of knowledge، and interior planning has entered the realm of modern planning methods. We believe that the differences in irregular shapes play a role in planning، concealing questions and objectives in the boundless spaces of interior design. They represent the most effective way to shape the structure of disparate shapes in accordance with their purpose in space planning، demonstrating the designer’s capabilities and the transfer of thought through the conceptual frameworks of the design tool. Because elements and foundations are the foundation of vital sub-connections in the design tool، and shape is one of its outcomes، they must be explored. The topic of the structure of irregular shapes in interior space is the result of a coherent، supportive effort to activate its visual and semantic properties. In this way، it raises numerous questions about its connections and organizational structures in order to activate them